Profiling post translational modification of histone and p53 in human breast carcinomas - Abdelghany, Magdy Korashy (2011)
Breast cancer is one of the most common cancers in females in the western world, and despite the advances in diagnosis and treatment it is still associated with significant morbidity. Thus, improvements to existing treatment modalities remain a priority. Understanding the molecular mechanisms controlling tumour growth and its modulation will be key to developing new therapies. In recent years it has been shown that posttranslational modifications (PTMs) of histones and p53 are functionally important in the regulation of cellular processes such as proliferation, differentiation and DNA damage repair. Thus, this study assessed the incidence of histone and p53 PTMs in breast tumours, and investigated how small molecule inhibitors of acetyltransferases can manipulate the levels of these PTMs in tumour cells. Our initial study demonstrated that hypoacetylation of H4K16 is associated with higher grade breast tumours (Elsheikh et al., 2009). Therefore, the expression levels of enzymes that are known to modulate H4K16 acetylation in vivo was assessed using immunohistochemical staining of 880 human breast tumour tissue microarrays. This led to the identification of a cluster of biomarkers (hMOF, H4K16ac, H3K9me3 and SUV39H1) which are significantly associated with patient outcome. We also assessed in tumours the incidence of other potential biomarkers including selected p53 PTMs such as p53K373ac and p53 K386ac. These were also found to be associated with favourable patient outcome in Kaplan-Meier survival analysis. Other potential biomarkers were also assessed such as the histone variant H2A.Z and its hyperacetylated form. H2A.Z correlated with Estrogen Receptor status of the tumours, consistent with a report that the gene encoding this histone variant is estrogen-regulated. In summary, this study has revealed that histone and p53 PTMs in breast tumours are potentially useful biomarkers for the classification of tumour type and as prognostic indicators, for use in conjunction with other clinicopathological indicators, and other well established biomarkers such as estrogen receptor and HER2. In a second aspect of the study, we investigated the effects of the acetyltransferase inhibitors curcumin and garcinol on a breast cancer cell model (MCF-7 cells). Garcinol blocked transcription-related PTMs such as H3K18ac, but surprisingly induced hyperacetylation of H4K16. This was found to be correlated with increased TIP60 expression, and correlated with increased incidence of DNA damage and cell cycle arrest. Other changes in cancer -associated PTMs were also observed, including increased H4K20 trimethylation. Garcinol compounds also reduced colony formation by MCF-7 cells and augmented sensitivity to etoposide. In summary, the data shows that histone and p53 PTMs constitute novel biological prognostic markers in breast cancer, and that targeting the enzymes that regulate these events may provide new avenues to drug therapies.